CULINARY AGROWISATA ATTRACTIVENESS AT RESTOURANT PALANTA LUBUAK SURIAN GUGUAK SUB DISTRICT LIMA PULUH KOTA DISTRICT WEST SUMATERA PROVINCE - Danil Novril; Kusai '; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research on culinary attractive is held on 27 February until 13 March 2017 in Lima Puluh Kota Regency West Sumatera. This study aims to determine the general description of culinary-specific agro-tourism and the attractiveness of culinary agro tourism as well as culinary-specific variations of fishery commodities. The method used is survey method by observation, documentation and interview. The results of this study indicate that the attractiveness of culinary agrowisata at the restourant Palanta Lubuak Surian is a typical eel minang cooking. Palanta Lubuak Surian restourant is one of the popular restourants in Lima Puluh Kota District. Restourant Palanta Lubuak Surian has beautiful natural panorama so many visitors who come to the restourant. In addition to beautiful natural panorama at the restourant Palanta Lubuak Surian good service, unique and interesting building form and access road smoothly / not difficult to visit. Restourant Palata Lubuak Surian also has a variety of menu such as fried fish, fish curry, vegetables, fried rubik, fried eggplant, jengkol curry and sambal lado tanak.Keywords: Attractiveness of Agro Tourism, Culinary, Palanta Lubuak Surian